Analysis Deformation Failure Characteristics and the Energy Evolution of Varying Lithologies under Cyclic Loading. (6th June 2022) - Liu, Jianqiang; Qin, Guangpeng; Cao, Jing; Zhai, Minghua
Abstract : Deep underground engineering often utilizes cyclic loading. To understand the deformation and damage characteristics of rock under cyclic loading conditions, cyclic loading tests of three different specimens with varying lithology were performed. The dissipated energy method was used to analyze the magnitude of damage and rock failure characteristics during the energy evolution process of cube specimens. The results indicated that the modulus of elasticity of three lithologies were stable prior and subsequent to cyclic loading. While the cyclic loading profile improved the rock's resistance to deformation, it increased the internal mesostructure defects. Rock damage caused by the cyclic loading reduced the uniaxial compression strength. This was especially true for coal samples. For coal samples, these observations were consistent with internal coal damage calculated by analysis. Under the same lithology and different loading modes, rock damage was caused by cyclic action, and the elastic strain energy released by instantaneous unloading of rock samples with significant damage was reduced. The rupture magnitude for cyclic loading was observed to be less than that of uniaxial compression. Under cyclic loading and varying different lithologies, sandstone absorbed the most energy, resulting in a larger final fracture magnitude compared to other lithologies.